Balancing and Conflict Between Work and Family Life of Sandwiched Caregivers: A Scoping Review - Ayumi Honda; Mayo Ono; Takahiro Nishida; Sumihisa Honda (Safety and Health at Work)
The aim of this scoping review was to advance our understanding of the balancing and conflict between work and family life experienced by sandwiched caregivers. Five online databases (CINAHL, MEDLINE, PubMed, SCOPUS, and Cochrane Library) were systematically searched between 20 Apr 2024 and 11 July 2024 for articles written in English and published between 1999 and July 2024, focused on the impact factors on work–family life balance and/or conflict of sandwiched caregivers. These database searches identified 58 citations, which resulted in 46 unique articles following the removal of duplicates. Title and abstract screening were identified for full-text review, twenty of these were excluded at full-text review, and leaving 13 articles for inclusion. We identified and categorized them into three key themes: (1) conflicts between work and family life and (2) impact of conflicts between work and family life on psychological well-being and (3) coping with conflicts between work and family life. The literature reviews suggested that the balance and conflict between work and family life were associated with work hours, flexibilities in work and workplace, and partner support in the sandwiched caregivers. Especially, flexible work arrangements and maintaining social connection were the stress-coping strategies for balancing work and family life. In an aging society, building a truly supportive and flexible workplace culture, along with increasing and utilizing formal care services for child-rearing and aged care, is more effective in promoting the well-being of sandwiched caregivers.